How Do we Measure Implementation of Inclusive Education in the Pacific Islands? A Process for Developing and Validating Disability-Inclusive Indicators. Issue 6 (2nd November 2018) - Sharma, Umesh; Jitoko, Filipe; Macanawai, Setareki S.; Forlin, Chris
Abstract: In recent years, countries of the Pacific have been moving strongly towards enhancing inclusive educational practices within a previously segregated education system. Through the Pacific Education Development Framework (PEDF) approved by 14 Pacific Island Education Ministers in 2009, the implementation of regional policies of inclusive education is a priority. To ensure that progress is measurable, these countries have been working collaboratively with several Australian institutions to develop a set of contextually appropriate indicators for measuring disability-inclusive education. This article describes the process adopted in developing these indicators and initial findings regarding the key outcomes. The research is guided by three key principles of collaboration, a need for systemic change and 'nothing about us without us'. The process adopts a three-stage approach which is outlined and key issues and implications discussed.